Khulu’ dalam Persfektif Hukum Islam - Suhendra, Darmiko (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2016)
Khulu' is the greatness of Islamic law in the fight for women's rights, so that if a wife is very tortured and there is no longer a sense of love and affection towards her husband, she can divorce her husband, even though divorce is hated by Allah. Khulu' also is divorce accompanied by a number of property as iwadh given by the wife to the husband in order to redeem themselves loose from marriage. Islamic law has given way to a wife who wants a divorce by filing khulu' as Islamic law gives way to the husband to divorce his wife by talak. Khulu' hated by the shari'ah as well as divorce. All sense and sense of well being refused khulu’, and only Allah that allow it to avert danger when it is unable to enforce Islamic laws. And the wisdom of khulu' is to avoid danger, namely the time of the quarrel that turmoil in a conjugal relationship until they could no longer united in the bonds of the household, then khulu’ allowed.